2014
DOI: 10.1128/ec.00094-14
|View full text |Cite
|
Sign up to set email alerts
|

Functional Implications and Ubiquitin-Dependent Degradation of the Peptide Transporter Ptr2 in Saccharomyces cerevisiae

Abstract: The peptide transporter Ptr2 plays a central role in di-or tripeptide import in Saccharomyces cerevisiae. Although PTR2 transcription has been extensively analyzed in terms of upregulation by the Ubr1-Cup9 circuit, the structural and functional information for this transporter is limited. Here we identified 14 amino acid residues required for peptide import through Ptr2 based on the crystallographic information of Streptococcus thermophilus peptide transporter PepT st and based on the conservation of primary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 56 publications
(77 reference statements)
1
8
0
Order By: Relevance
“…Such a combination has been identified for the stress-induced endocytosis of Gap1 that can be mediated by Bul1, Bul2, Aly1/Art6, or Aly2/Art3 (43). Recently, Kawai and colleagues (44) documented that the addition of cycloheximide to cells grown in synthetic dextrose (S.D.) medium triggers Rsp5-dependent ubiquitylation and endocytosis of Ptr2.…”
Section: Fig 4 Loss Of Bul1 and Bul2 Function Results In Vacuolar Dmentioning
confidence: 99%
“…Such a combination has been identified for the stress-induced endocytosis of Gap1 that can be mediated by Bul1, Bul2, Aly1/Art6, or Aly2/Art3 (43). Recently, Kawai and colleagues (44) documented that the addition of cycloheximide to cells grown in synthetic dextrose (S.D.) medium triggers Rsp5-dependent ubiquitylation and endocytosis of Ptr2.…”
Section: Fig 4 Loss Of Bul1 and Bul2 Function Results In Vacuolar Dmentioning
confidence: 99%
“…This finding helped to explain why cycloheximide had little effect on amino acid secretion (Figure B), even though one would expect significant depletion of Ptr2p after 90 min with no protein synthesis [the natural lifetime of Ptr2p is about 1 h (Kawai et al ., )]. Apparently the peptides responsible for all secreted leucine were loaded in the cell in the first 30 min, and it was the amount of active Ptr2p in this time window that determined how much secreted leucine was observed at the end of the 90 min interval.…”
Section: Resultsmentioning
confidence: 99%
“…Less is known about post-transcriptional regulation of PTR2, although several genes involved in maturation of PTR2 mRNA and in Ptr2p trafficking have been identified (Cai et al, 2006). It was also shown that, when Ptr2p expression is induced with amino acids, the protein undergoes rapid turnover mediated by ubiquitylation and degradation (Kawai et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Upon reexamination of micrographs presented in earlier reports on receptor and transporter down-regulation, we found that some internalized surface polytopic proteins appear on lysosome membranes en route to the lumen for degradation, e.g. the high affinity tryptophan permease Tat2 ( Beck et al, 1999 ), glucose transporters Hxt1 and Hxt3 ( O’Donnell et al, 2015 ), peptide transporter Ptr2 ( Kawai et al, 2014 ), and myo-inositol transporter Itr1 ( Nikko and Pelham, 2009 ). We also noticed that most of these published studies do not directly assess whether ESCRTs are required for protein degradation.…”
Section: Introductionmentioning
confidence: 69%